A late IL‐33 response after exposure to Schistosoma haematobium antigen is associated with an up‐regulation of IL‐13 in human eosinophils. (1st July 2013) - Wilson, S.; Jones, F. M.; Fofana, H. K. M.; Landouré, A.; Kimani, G.; Mwatha, J. K.; Sacko, M.; Vennervald, B. J.; Dunne, D. W.
Summary IL‐33, a proposed alarmin, stimulates innate immune cells and Th2 cells to produce IL‐13 and is rapidly upregulated upon antigen exposure in murine helminth infection. The human IL‐33 response to helminth antigen was analysed in Malians infected with Schistosoma haematobium by disrupting parasite integrity via chemotherapy. Plasma IL‐33 was measured pretreatment, and 24 h and 9 weeks post‐treatment. At 24 h post‐treatment, IL‐33 levels were low. Nine week post‐treatment IL‐33 levels were elevated and were associated with an increase in intracellular IL‐13 in eosinophils. Up‐regulation of intracellular IL‐13 in eosinophils was also associated with eosinophil expression of ST2L, the IL‐33 receptor. IL‐33 may play an important downstream role in the human response to schistosome adult worm antigen exposure.